From Hashtag to Street Action: Applying SIMCA to the #IndonesiaGelap Movement in Samarinda - Dhia Fachirah Chairunnisa; Niken Nurmiyati; Sanny Nofrima; Muhammad Reza Fahlevy; Dea Rizky Amalia (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2025)
This study examines #IndonesiaGelap as a digitally mediated new social movement through which Indonesians expressed dissatisfaction with contested government policies, focusing on mobilization in Samarinda. It aims to explain how affective expressions and moral evaluations circulating online contributed to collective identity formation and the translation of online resonance into offline collective action. Using a qualitative case-study design, data were drawn from in-depth interviews with movement participants, participatory observation, social media content (X and Instagram), and news coverage. Materials were analysed thematically and interpreted through the Social Identity Model of Collective Action (SIMCA), complemented by resource mobilization theory and Alfred Schutz’s phenomenological concepts of motive and intersubjectivity. Findings show that perceived injustice created a shared moral frame, while digitally amplified anger, outrage, and hope fostered solidarity and an inclusive coalition identity across student organizations, civil society groups, and unaffiliated citizens. Collective efficacy was enacted through open consolidations and coordinated mobilization of material, human, organizational, and symbolic resources, including the hashtag and Garuda imagery. The study concludes that #IndonesiaGelap in Samarinda was not merely a trending hashtag but a meaning-making process in which platformed emotions, identity alignment, and resource coordination jointly enabled offline collective action. The contribution lies in specifying how affective dynamics and morality operate within SIMCA in an Indonesian local context, and in showing how efficacy is organizationally produced. Practically, the results imply that transparent, participatory policymaking and responsive communication may reduce escalation, while movement organizers benefit from inclusive consolidation and clear symbolic strategies.